2013
DOI: 10.5370/jeet.2013.8.3.453
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Wind Power Integration on Generation Dispatch in Power Systems

Abstract: -The probabilistic nature of renewable energy, especially wind energy, increases the needs for new forms of planning and operating with electrical power. This paper presents a novel approach for determining the short-term generation schedule for optimal operations of wind energy-integrated power systems. The proposed probabilistic security-constrained optimal power flow (P-SCOPF) considers dispatch, network, and security constraints in pre-and post-contingency states. The method considers two sources of uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In [5], an impact of wind power integration on generation dispatch in power systems is investigated. As sharing of wind generations increase, they should not only generate electrical power, but also contribute other functions.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], an impact of wind power integration on generation dispatch in power systems is investigated. As sharing of wind generations increase, they should not only generate electrical power, but also contribute other functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, wind power generation is unsteady and uncontrollable because wind speed inherently depends on natural meteorological conditions. Moreover, the introduction of large amounts of intermittent power to the grid can bring about serious technical challenges such as grid interconnection, power quality, and system reliability [4,5]. Therefore, wind farm (WF) developers need to overcome the intermittent nature of wind power before attempting to dispatch high levels of power to the grid.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the continuing integration of new large WFs into the power systems can influence the stabilities of power systems [3,4].…”
Section: Introductionmentioning
confidence: 99%